The Role of Midwives on Mother's Mental Health in the First 1000 Days of Life - Aulia, Dinda; Jayanti, Ratna Dwi; Pasca Wardhana, Manggala; Farida Sembiring, Ella; Djaguna, Nurafmi; Fitriana, Farida; Azizah , Nurul (Jurnal MIDPRO, 2023)
The first 1000 days of life is a transitional period from conception to two years after giving birth, a time when a woman experiences changes in roles and responsibilities. This period is a vulnerable time for women to experience mental health problems such as stress and anxiety which also increase the risk of depression. To assess non-pharmacology interventions that can prevent or reduce maternal mental health problems in the first 1000 days, especially that the midwife can provide. Design: A literature review of systematic review Data sources: PubMed, Science Direct, Epistemonikos, and website searching. Methods: literature searching used advanced search with the Boolean operator, truncation, and MeSH terms. The criteria included articles published in 2021, the use of Bahasa and English, open access, describing mental health issues (stress, anxiety, depression) in the first 1000 days, and giving information about the non-pharmacology intervention that a midwife can provide. The flow of literature searching used the PRISMA diagram and assessed with the Critical Appraisal Skills Program checklist. Findings: 235 articles were obtained and four studies were included in this review that discusses maternal mental health with different periods and variations of intervention. To inform sources of maternal mental health problems, the effect on mother and child, the effect of an intervention, and the role of a midwife. Conclusion: all of the interventions have a different effect in each period of the first 1000 days, but are still helpful for the mother. Cognitive Â Â Behavioral Therapy has a dominant effect to prevent or reduce maternal mental health problems. Midwives can provide intervention by enhancing their knowledge and skill, also needs support from the organization profession. This intervention needs to integrate into routine maternal care to give optimum results.